The Frontiers of Citizenship
XXI, 210 p.
Keywords: Who is entitled to be a citizen? What rights and duties does citizenship involve? These political questions are being asked today with a renewed urgency, both by practising politicians and by scholars. These essays by distinguished contributors examine the changing frontiers of modern citizenship. They look at the way citizenship is being reshaped within the nation state, in relations between women and the state, under the impact of economic crisis and recession, and in the face of new multinational political forces.